Baby-sitters little sister. 3, Karen's worst day - Martin, Ann M., 1955-; Farina, Katy (Farina, Katy. Baby-sitters little sister., 2021)
Another graphic novel in this fun series spin-off of The Baby-sitters Club, featuring Kristy's little stepsister! Karen is having a terrible day. Her favorite jeans are missing, there's no prize in the Crunch-O cereal box, and Boo-Boo the cat won't play with her. She even gets punished and sent to her room! Karen tries everything to make her day better, but nothing is going right and her bad luck just won't go away. Will this be the worst day ever?